Metody pomiaru podobieństwa nieruchomości w procesie wyceny w podejściach porównawczym i dochodowym - Lis, Christian (Methods of Measurement of Real Estates Similarity in the Comparative and Income Procedure of Valuation, 2007)
There are two procedures of real estate valuation in Poland, that give us market value: comparative and income procedure. In both cases information is used about prices, rents and attributes of similar immobilities. Problem is that in process of valuation attributes measured on different scales (nominal, ordinal, rational) have to be taken into account. In the paper results of measurement of similarity of different kinds of real estates were presented using taxonomic measure of similarity and generalized distance measure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 445-453